MODERASI BERAGAMA DALAM PERGESERAN POLA DAKWAH MILENIAL MELALUI KEGIATAN DI MASJID - Munawati, Siti; Rahmatullah, M Asep (ISLAMIKA, 2022)
The center for the development of religious moderation in the mosque can become a center of information, a place for managing all matters so that the mosque becomes a source of knowledge, a source of reading and a source of warnings, advice and direction in the form of da'wah. The shift in da'wah patterns for the millennial generation coincides with technological advances that make things easier, so that strategies, methods and media are needed to spread da'wah. And all of its activities aim to invite the millennial generation to good and forbid evil. The emergence of the millennial generation Islamic community is an attraction and a challenge for the millennial generation in understanding and implementing Islamic religious values ​​that have been conveyed through da'wah in accordance with the conditions and phenomena after the Covid-19 pandemic. The research methodology was carried out based on the purpose of writing, in the form of field research, using a descriptive qualitative approach that is conceptually adequate about specifics, topics, subjects, and targets. The displacement of people's lives in the digital era has changed a new order of life that ignores geographical, cultural, political and economic boundaries, which emphasizes the flow of information and communication. The challenge of religious moderation in digital preaching for millennials and other social media users has social implications in society. Various positive and negative impacts arising from positive impacts include making it easier to get information, being able to join the community, and being able to actualize. And social media preachers are one of the reference choices for the Muslim middle class who are religious. And many of the preachers have a special team to document social media as one of the reference choices for the religious Muslim middle class. As a result, humans can interact in almost all corners of the world, free of charge, and the sophistication of this technology brings them closer without distance Keywords: Mosques, Moderation, Millennials, Media, Da'wah